International Consensus on drug allergy. Issue 4 (21st February 2014) - Demoly, P.; Adkinson, N. F.; Brockow, K.; Castells, M.; Chiriac, A. M.; Greenberger, P. A.; Khan, D. A.; Lang, D. M.; Park, H.‐S.; Pichler, W.; Sanchez‐Borges, M.; Shiohara, T.; et al.
Abstract When drug reactions resembling allergy occur, they are called drug hypersensitivity reactions (DHRs) before showing the evidence of either drug‐specific antibodies or T cells. DHRs may be allergic or nonallergic in nature, with drug allergies being immunologically mediated DHRs. These reactions are typically unpredictable. They can be life‐threatening, may require or prolong hospitalization, and may necessitate changes in subsequent therapy. Both underdiagnosis (due to under‐reporting) and overdiagnosis (due to an overuse of the term 'allergy') are common. A definitive diagnosis of such reactions is required in order to institute adequate treatment options and proper preventive measures. Misclassification based solely on the DHR history without further testing may affect treatment options, result in adverse consequences, and lead to the use of more‐expensive or less‐effective drugs, in contrast to patients who had undergone a complete drug allergy workup. Several guidelines and/or consensus documents on general or specific drug class‐induced DHRs are available to support the medical decision process. The use of standardized systematic approaches for the diagnosis and management of DHRs carries the potential to improve outcomes and should thus be disseminated and implemented. Consequently, the International Collaboration in Asthma, Allergy and Immunology (iCAALL), formed by the European Academy of Allergy and Clinical Immunology (EAACI), the American Academy of Allergy, Asthma and Immunology (AAAAI), the American College of Allergy, Asthma and Immunology (ACAAI), and the World Allergy Organization (WAO), has decided to issue an International CONsensus (ICON) on drug allergy. The purpose of this document is to highlight the key messages that are common to many of the existing guidelines, while critically reviewing and commenting on any differences and deficiencies of evidence, thus providing a comprehensive reference document for the diagnosis and management of DHRs.